A Comparative Study Between the Carpet of Prominent Figures or Mashahir Carpet Woven in the Carpet Workshop of Mousavi Sirat and the Milani Factory of Kerman by Applying Discourse Analysis (DA) - Sahel Erfanmanesh (هنر و تمدن شرق, 2023)
In contemporary times, many artworks from the Qajar era are being regenerated in various art fields, including carpet weaving. The carpet of Mashahir (the figure of famous people) woven in the Milani factory is another example of artwork from the Qajar era, which was designed and woven again by Mousavi Sirat after the Islamic Revolution of Iran. Considering the changes in the reproduction of the carpet and pointing to the research objectives, which deal with the differences between the two carpets according to the common signs and discourse of each time, this study aims to: 1. address the possible differences and similarities between these two carpets, and 2. evaluate the influence of different signs and textures in these carpets on the interpretation of the carpet in two different discourses. This study is a descriptive-analytical and comparative research method based on library data. The research findings indicate that the signs and symbols used in the carpet of the Milani factory represent the identity of individuals, and they are considered the main elements of the artwork rather than merely decoration items. In the contemporary era, it is difficult to identify famous figures if these symbols are removed or replaced. Given that the carpet of the Milani factory was created with respect to political-cultural considerations, the identification of each figure in the carpet is of great importance. In addition, to accurately represent the physical characteristics of people, some symbols have been used to introduce them better. In the contemporary carpet, it seems that according to the discourse of neo-Qajarism, the aim of weaving the second work was to regenerate merely a work of the Qajar era, as targeting the identity of the individuals was not very significant.